Prognostic role of CD74, CD10 and Ki-67 immunohistochemical expression in patients with diffuse malignant peritoneal mesothelioma: a retrospective study - Yufei Liang; Chunying Li; Yingying Liu; Liang Tian; Dongliang Yang (BMC Cancer, 2023)
Abstract Background Diagnosis and treatment of diffuse malignant peritoneal mesothelioma (DMPM) are still challenging. The aim of the present study was to explore the correlation between CD74, CD10, Ki-67 and clinicopathological parameters, and identify independent prognostic factors of DMPM. Methods Seventy patients with pathologically proven DMPM were retrospectively reviewed. The expression of CD74, CD10 and Ki-67 in peritoneal tissues was detected by immunohistochemical analysis using standard avidin biotin complex (ABC) immunostaining technique. Kaplan-Meier survival analysis and multivariate Cox regression analyses were performed to assess prognostic factors. The nomogram based on the Cox hazards regression model was established. C-index and calibration curve were performed to evaluate the accuracy of nomogram models. Results The median age of DMPM was 62.34 years, and the male-to-female ratio was 1: 1.80. CD74 expression was identified in 52 (74.29%) of 70 specimens, CD10 in 34 (48.57%) specimens, and higher Ki-67 in 33(47.14%) specimens. CD74 was negatively associated with asbestos exposure(r = -0.278), Ki-67(r = -0.251) and TNM stage(r = -0.313). All patients were effectively followed up in the survival analysis. Univariate analysis revealed that PCI, TNM stage, treatment, Ki-67, CD74 and ECOG PS were associated with DMPM prognosis. CD74 (HR = 0.65, 95%Cl:0.46–0.91, P = 0.014), Ki-67(HR = 2.09, 95%Cl:1.18–3.73, P = 0.012),TNM stage (HR = 1.89, 95%Cl:1.16–3.09, P = 0.011), ECOG PS(HR = 2.12, 95%Cl:1.06–4.25, P = 0.034), systemic chemotherapy (HR = 0.41, 95%Cl:0.21–0.82, P = 0.011) and intraperitoneal chemotherapy (HR = 0.34, 95%Cl:0.16–0.71, P = 0.004) were independent predictors by multivariate Cox analysis. The C‑index of the nomogram for predicting overall survival (OS) was 0.81. The OS calibration curve showed good agreement between nomogram-predicted and observed survival. Conclusions CD74, Ki-67, TNM stage, ECOG PS and treatment were independent factors affecting prognosis of DMPM. Reasonable chemotherapy treatment might improve the prognosis of patients. The proposed nomogram was a visual tool to effectively predict the OS of DMPM patients.